2010
DOI: 10.1590/s0102-311x2010000300014
|View full text |Cite
|
Sign up to set email alerts
|

Gravidez na adolescência e outros fatores de risco para mortalidade fetal e infantil no Município do Rio de Janeiro, Brasil

Abstract: This article analyzes teenage pregnancy and other risk factors for fetal and infant mortality in the city of Rio de Janeiro, Brazil. The study included a sample of births in Rio de Janeiro, and exposure variables were organized hierarchically. For fetal death, the results showed the protective effect of adequate prenatal care, while maternal morbidity increased the risk. For neonatal death, adequate prenatal care and female gender in the newborn were protective factors, while black or brown maternal skin color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
1
45

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 30 publications
(36 reference statements)
5
27
1
45
Order By: Relevance
“…Dentre as hemorragias, ressalta-se a presença de trombofilias em pacientes com histórico de abortos recorrentes e perdas fetais, identificando-se a associação entre fatores trombogênicos e má história obstétrica. A literatura propõe investigação de rotina para trombofilias em mulheres que já sofreram abortos, considerando a possibilidade de tratamento com heparina de baixo peso molecular durante a gravidez atual, evitando efeitos deletérios desta associação (19) . O diabetes gestacional é uma intercorrência frequente no ciclo grávido-puerperal e que apresenta alta incidência de morbimortalidade fetal e neonatal.…”
Section: Discussionunclassified
“…Dentre as hemorragias, ressalta-se a presença de trombofilias em pacientes com histórico de abortos recorrentes e perdas fetais, identificando-se a associação entre fatores trombogênicos e má história obstétrica. A literatura propõe investigação de rotina para trombofilias em mulheres que já sofreram abortos, considerando a possibilidade de tratamento com heparina de baixo peso molecular durante a gravidez atual, evitando efeitos deletérios desta associação (19) . O diabetes gestacional é uma intercorrência frequente no ciclo grávido-puerperal e que apresenta alta incidência de morbimortalidade fetal e neonatal.…”
Section: Discussionunclassified
“…White race prevailed in the subject municipality and the 2010 Brazilian census confirmed that the white population in the state of Paraná was 7,344,122 individuals, while the sum of the other races was 3,100,404 -virtually three times more (25) . In the literature, however, the brown and black races, added to the population with a lower socioeconomic level, present the highest infant death index (22) . Good vitality conditions at birth such as an Apgar score higher than seven, proper weight at birth, and gestational age ≥37 weeks occurred to most of the children that died in the neonatal and post-neonatal period in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Virtually all deliveries were in a hospital environment. However, although deliveries are assisted by professionals and have access to intensive care services, extending the children's lifetime and reducing deaths, quality in the delivery care is crucial, considering that most of the newborns' diseases in Brazil are related to inefficacious and inefficient obstetric care (11,(21)(22) . In this setting the health team must be ready to provide care for cardiopulmonary resuscitation in the delivery room to prevent perinatal asphyxia and/or anoxia; this is an important mechanism to reduce neonatal mortality (23) .…”
Section: Discussionmentioning
confidence: 99%
“…A mortalidade infantil, por constituir-se um grave problema de saúde pública, demanda investimentos na melhoria geral das condições de vida da população, incluindo a reestruturação da assistência prestada à gestante e recém-nascido, com articulação entre os serviços de atenção básica e os de assistência ao parto; garantindo o acesso igualitário à qualidade do pré-natal e ao processo de parto, nascimento e hospitalização do recém-nascido (19) . Apesar do não ter sido encontrada associação entre número de consultas de pré-natal e óbitos, autores destacam que não fazer o pré-natal aumenta o risco para a ocorrência de perdas fetais, óbitos infantis e baixo peso ao nascer (20)(21)(22) . Assim, ressalta-se a importância da qualidade da assistência para identificação precoce das gestantes de risco (23) .…”
Section: Discussionunclassified
“…Apesar da não associação entre óbito do recém-nascido com a pouca idade materna, autores apontam que filhos de adolescentes apresentam maior risco de morte no primeiro ano de vida (21) . Frente a isto, faz-se necessá-rio que os profissionais de saúde criem vínculo efetivo com as mães adolescentes, incluído as famílias dessas jovens na assistência, favorecendo o diálogo e contribuindo para fortalecer o apoio familiar.…”
Section: Discussionunclassified